Mbaru Gendang sebagai Ruang Publik Menurut Jürgen Habermas dalam Menyelesaikan Persoalan Konflik Tanah di Manggarai - Masut, Vinsensius Rixnaldi; Cancang, Elfridus; Riyanto, FX Armada (Lembaga penelitian dan pengabdian kepada Masyarakat, 2023)
This study aims to explain the function of the Mbaru Gendang as a public sphere in resolving land conflicts in Manggarai. The Mbaru Gendang as the traditional house of the Manggarai people has become a central place in every public policy making, including in resolving land conflicts. Manggarai people's awareness of the function of the Mbaru Gendang can be explored more deeply by using Jurgen Habermas' philosophy about public sphere. According to Habermas, a public sphere is not just there for locative information, but a condition that enables a joint discourse, openly and freely, for the sake of reaching a public decision. Thus, a public sphere is conditioning rational communication and dialogue through a discursive process. The methodology used in this study is qualitative phenomenological by conducting interviews with Manggarai traditional leaders. The results of the interviews are then elaborated with Habermas' philosophy about public sphere. The finding of this study is that the Mbaru Gendang has become a space for discourse in resolving land conflicts in Manggarai. This issue requires open and free rational communication and dialogue.